Vtip a náboženství: posvátno jako mysterium ludicrum et ridiculum = Jokes and religion : the sacred as a mysterium ludicrum et ridiculum - Chlup, Radek (Religio, 2005)
The article investigates the meaning of jokes in religion. Building up on Mary Douglas' classic analysis, it sees the essence of a joke in its ability to bring in relation disparate elements in such a way that one accepted pattern is challenged by the appearance of another, making us realize that the accepted pattern has no necessity, that any particular ordering of experience may be arbitrary and subjective. The reason why jokes often appear in religion is that here, too, we see an attempt at transcending established patterns and getting in touch with what is beyond them. For while religion and ritual help to define the categories and structural principles that a society stands upon, they also make it possible to transcend them. As Victor Turner has shown, any given social order has its limits and there are always events and situations incongruous with it, thus threatening its very existence. Religion helps to avoid this threat in that it not just establishes social orders, but also makes us glimpse their fragility and dependence on what transcends them. Religion acts not just as a supporter of order, but as an interface between order and chaos, structure and liminality. This is why it makes use of jokes, which have the same ability.